Cultural competence in mental health nursing: validity and internal consistency of the Portuguese version of the multicultural mental health awareness scale—MMHAS. Issue 1 (December 2016) - de Almeida Vieira Monteiro, Ana; Fernandes, Alexandre
Abstract Background Cultural competence is an essential component in rendering effective and culturally responsive services to culturally and ethnically diverse clients. Still, great difficulty exists in assessing the cultural competence of mental health nurses. There are no Portuguese validated measurement instruments to assess cultural competence in mental health nurses. This paper reports a study testing the reliability and validity of the Portuguese version of the Multicultural Mental Health Awareness Scale–MMHAS in a sample of Portuguese nurses. Methods Following a standard forward/backward translation into Portuguese, the adapted version of MMHAS, along with a sociodemographic questionnaire, were applied to a sample of 306 Portuguese nurses (299 males, 77 females; ages 21–68 years, M  = 35.43, SD  = 9.85 years). A psychometric research design was used with content and construct validity and reliability. Reliability was assessed using internal consistency and item–total correlations. Construct validity was determined using factor analysis. Results The factor analysis confirmed that the Portuguese version of MMHAS has a three-factor structure of multicultural competencies (Awareness, Knowledge, andSkills ) explaining 59.51 % of the total variance. Strong content validity and reliability correlations were demonstrated. The Portuguese version of MMHAS has a strong internal consistency, with a Cronbach's alpha of 0.958 for the total scale. Conclusions The results supported the construct validity and reliability of the Portuguese version of MMHAS, proving that is a reliable and valid measure of multicultural counselling competencies in mental health nursing. The MMHAS Portuguese version can be used to evaluate the effectiveness of multicultural competency training programs in Portuguese-speaking mental health nurses. The scale can also be a useful in future studies of multicultural competencies in Portuguese-speaking nurses.